2021
DOI: 10.1111/pcn.13300
|View full text |Cite
|
Sign up to set email alerts
|

Current findings and perspectives on aberrant neural oscillations in schizophrenia

Abstract: There is now consistent evidence that neural oscillation at low‐ and high‐frequencies constitute an important aspect of the pathophysiology of schizophrenia. Specifically, impaired rhythmic activity may underlie the deficit to generate coherent cognition and behavior, leading to the characteristic symptoms of psychosis and cognitive deficits. Importantly, the generating mechanisms of neural oscillations are relatively well‐understood and thus enable the targeted search for the underlying circuit impairments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 200 publications
(223 reference statements)
3
53
0
Order By: Relevance
“…In summary, our results reveal circuit mechanisms which switch the prefrontal cortex from maintaining to updating behavioral strategies, functions for interhemispheric GABAergic projections in the neocortex, roles for gamma synchrony in information processing beyond communication through coherence, and new forms of network plasticity. These findings identify a new callosal connection originating from prefrontal parvalbumin neurons as a critical circuit locus for understanding and modulating the deficits in gamma synchrony and behavioral flexibility that are major features of schizophrenia 910 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In summary, our results reveal circuit mechanisms which switch the prefrontal cortex from maintaining to updating behavioral strategies, functions for interhemispheric GABAergic projections in the neocortex, roles for gamma synchrony in information processing beyond communication through coherence, and new forms of network plasticity. These findings identify a new callosal connection originating from prefrontal parvalbumin neurons as a critical circuit locus for understanding and modulating the deficits in gamma synchrony and behavioral flexibility that are major features of schizophrenia 910 .…”
Section: Discussionmentioning
confidence: 88%
“…Thus, callosal parvalbumin projections switch prefrontal circuits from maintaining to updating behavioral strategies by synchronizing callosal communication and preventing it from inappropriately maintaining outdated neural representations. These findings may explain how deficits in prefrontal parvalbumin neurons and gamma synchrony cause impaired behavioral flexibility in schizophrenia 910 , and identify long-range projections from prefrontal parvalbumin neurons as a key circuit locus for understanding and treating these deficits.…”
mentioning
confidence: 92%
“…More importantly, abnormalities in gamma-band oscillations are linked to current evidence from postmortem, genetic, and animal model studies that have implicated alterations in GABAergic interneurons and glutamatergic neurotransmission in schizophrenia. 67 For clinically relevant research, pharmacokinetic studies using PET showed increased D2 dopamine receptor (D2R) drug occupancy in the striatum of patients with schizophrenia, which provided one of the bases for the "dopamine hypothesis," a fundamental theory associated with treatment with antipsychotics. 79 PET studies also revealed that D2R drug occupancy needs to be maintained at 65-80% ("therapeutic window") to ensure a good balance between producing extrapyramidal syndromes and antipsychotic effects.…”
Section: Neuroimaging and Neurophysiological Approachesmentioning
confidence: 99%
“…17 Specifically, patients are treated at the initial stage, when optimal treatment responsiveness is expected, and the response to the treatment is accurately and objectively evaluated 61,62,21,63,64 In addition, the recent development of brain imaging techniques has enabled us to view the structure, function, and chemical/metabolic composition of the brain in living subjects. While numerous diagnostic measures, such as salivary cortisol levels and blood markers of inflammation and oxidation, have been proposed for use in the context of schizophrenia 21,65 neuroimaging and neurophysiological methods, especially magnetic resonance imaging (MRI) and electroencephalography (EEG)/magnetencephalography (MEG), are potential diagnostic approaches with which we have accumulated much knowledge because of their noninvasiveness and frequent use in clinical settings 66,67 In addition, magnetic resonance spectroscopy (MRS) and positron emission tomography (PET) enable us to evaluate abnormalities in chemical and metabolic changes in patient brains while they are living.…”
Section: Neuroimaging and Neurophysiological Approachesmentioning
confidence: 99%
“…In humans, alterations in excitatory/inhibitory balance, neurodevelopmental processes and neuromodulation have been identified at cellular, molecular and synaptic level [ 150 ]. At the systems level, alterations in functional connectivity and synchrony, resulting in aberrant gamma oscillations in cognitive and sensory brain areas, have been shown to be present since the early onset of the disorder [ 151 , 152 ]. The neuronal circuits underlying such alterations remain largely to be identified, and a clear etiopathogenetic mechanism underlying SCZ is still missing.…”
Section: Light-based Brain Circuit Analysis and Modulation In Patholo...mentioning
confidence: 99%